2014
DOI: 10.1515/ijamh-2013-0309
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempts and suicides in Bolivia from 2007 to 2012: pesticides are the preferred method – females try but males commit suicide!

Abstract: More females attempted suicide, whereas more males realized suicide. Suicide attempts were most numerous among adolescents in contrast to suicides being most prevalent in the older age groups. Self-poisoning with pesticides was the most popular method used. Access to potential suicide materials should be restricted and psychosocial interventions initiated to prevent suicides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 10 publications
0
14
0
2
Order By: Relevance
“…[ 6 8 ] The other modes of DSH reported were near hanging, self-immolation, jumping from heights, self-infliction, inhalation of automobile gases, etc. [ 6 8 9 10 ] The less frequently reported modes of DSH in this study were consumption of plant poisons (7.8%), near hanging (5.3%), corrosive chemical ingestion (4.7%), and ingestion of rat killer poisons (4.2%). Multiple modes of DSH were observed in 3 patients, one patient presented with near hanging after consuming insecticide poison, the second patient consumed a combination of kerosene, insecticide and paint and the third patient consumed zinc phosphide along with paracetamol tablets.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…[ 6 8 ] The other modes of DSH reported were near hanging, self-immolation, jumping from heights, self-infliction, inhalation of automobile gases, etc. [ 6 8 9 10 ] The less frequently reported modes of DSH in this study were consumption of plant poisons (7.8%), near hanging (5.3%), corrosive chemical ingestion (4.7%), and ingestion of rat killer poisons (4.2%). Multiple modes of DSH were observed in 3 patients, one patient presented with near hanging after consuming insecticide poison, the second patient consumed a combination of kerosene, insecticide and paint and the third patient consumed zinc phosphide along with paracetamol tablets.…”
Section: Discussionmentioning
confidence: 73%
“…[ 7 ] Insecticide poisoning and self-immolation were associated with high mortality rate in India while in a South American country hanging and jumping from heights had a bad outcome. [ 8 9 10 ] A wide variety of poisons like insecticides, pesticides, plant poisons, rodenticides is freely available across the country. Even drugs such as benzodiazepines, barbiturates, and antidepressants are easily accessible.…”
Section: Introductionmentioning
confidence: 99%
“…The data from Kampala showed that pesticides were responsible for a majority of poisonings in the hospitals, which is consistent with studies from other low-and middle-income countries, where pesticides are easily available in retail shops and sold in the streets. 3,17,18 Men were more numerous both among self-harm and unintentional cases of poisoning. This might be due to men more often handling pesticides and therefore being more prone to occupational poisonings and, due to easy accessibility, also self-harm.…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization, every 40 seconds, a person commits suicide being the second leading cause of death among 15-29 year old 1,2 . High suicidality rates are a widespread concern, particularly in Western 3 and Central Europe 4 , the U.S. 5 , Asiatic countries such as Russia and former Socialist Republics 6 , South Korea 6 , China 7 , India 8 , Sri Lanka 9 ; and Latin American countries such as Cuba 10 , Uruguay 11 ; Ecuador 12 , Bolivia 13 , Brazil 14 , Argentina 15 and Colombia 16 . Suicide risk increases in people with mental disorders or impulsive behavior, those facing stressful situations or with easy access to harmful tools such as poisoning, hanging and firearms 17 .…”
Section: Introductionmentioning
confidence: 99%